Influence of Fixation Products Used in the Histological Processing in the FTIR Spectra of Lung Cells. Issue 5 (11th July 2012) - Pereira Pereira, Thiago Martini Thiago Martini; Dagli Dagli, Maria Lucia Zaidan Maria Lucia Zaidan; Mennecier Mennecier, Grégory Grégory; Zezell Zezell, Denise Maria Denise Maria
Abstract : The aim of the present study is to evaluate the differences on FTIR spectra of the normal lung cell (noncancerous mice lung epithelial cell line e10) due to different fixation protocols for histological processing. The results shown that formalin and methacarn (normally used in fixation) did cause many changes on the FTIR spectra of mice lung cells e10, mainly in the organic compounds (800–1800 cm −1 ) in lipids, DNA, and proteins, and the alcohol 70% fixation protocol caused almost no changes on the FTIR spectra compared to unfixed cells spectra (in PBS). It can be concluded that histological processing with alcohol 70% fixation protocol can be used in the FTIR study of mice lung cell line e10.